2011
DOI: 10.1590/s1806-37132011000600013
|View full text |Cite
|
Sign up to set email alerts
|

Modelo experimental ex vivo com bloco pulmonar dividido

Abstract: Since they were first established, ex vivo models of lung reconditioning have been evaluated extensively. When rejected donor lungs are used, the great variability among the cases can hinder the progress of such studies. In order to avoid this problem, we developed a technique that consists of separating the lung block into right and left blocks and subsequently reconnecting those two blocks. This technique allows us to have one study lung and one control lung.Keywords: Lung transplantation; Transplantation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In Brazil, clinical and experimental studies utilized the EVLP technique with the objective of both evaluation and pulmonary reconditioning. ( 4 , 16 18 )…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, clinical and experimental studies utilized the EVLP technique with the objective of both evaluation and pulmonary reconditioning. ( 4 , 16 18 )…”
Section: Introductionmentioning
confidence: 99%
“…14 The oxygenation capacity during the ex vivo perfusion can be considered to be the most important parameter for functional assessment, since it reflects both gas exchange and graft performance. Previous studies have shown that PaO 2 values correspond more reliably to the quality of lung preservation than do other parameters such as those from pathology or radiology.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007 we began preparations for EVLP via training courses and experimental studies with lungs rejected for transplantation. We initially sought to establish our methodology 15 , 16 , then tested lung preservation solutions 17 and static or continuous topical preservation methodologies 18 . This prepared us to perform the first lung transplantation using EVLP in Brazil in 2012.…”
mentioning
confidence: 99%